WELL BEGUN IS HALF DONE: KEEPING THE SPARKS FLYING DURING ENGLISH LESSONS - Tono Suwartono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
Opening plays a very crucial period in the course of a lesson. Just like other expressions to illustrate the energy it gives, the analogies could be â€œLove at the first sightâ€, or, â€œFirst impression (of you) is so exciting, the rest is up to youâ€. Lessons opening, when it is made beneficial to the students, serves as a fire trigger, providing them with strong power at the start, and sustains â€œeternal flameâ€ till the end of the lesson. This article argues the rationale behind it and presents some ways of creating such lessons opening in the context of English language teaching.